2019
DOI: 10.1371/journal.pntd.0007389
|View full text |Cite
|
Sign up to set email alerts
|

A 15-year review of dengue hospitalizations in Singapore: Reducing admissions without adverse consequences, 2003 to 2017

Abstract: Objectives Since the 1990s, Singapore has experienced periodic dengue epidemics of increasing frequency and magnitude. In the aftermath of the 2004–2005 dengue epidemic, hospitals refined their admission criteria for dengue cases to right-site dengue case management and reduce the burden of healthcare utilization and negative outcomes. In this study, we describe the national trends of hospital admissions for dengue and disease severity in terms of length of stay (LOS), admission to the intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
3
25
1
Order By: Relevance
“…With these criteria, the number of unnecessary hospitalisation was drastically reduced, without a concomitant increase in adverse clinical outcomes. 132 In the following, we focus on the management of severe dengue to reduce mortality. Every travel medicine provider and physician caring for ill returned travellers should be familiar with the clinical management of increased vascular permeability leading to intravascular volume depletion is the hall mark of severe dengue, which may progress to life-threatening dengue shock syndrome.…”
Section: Clinical Manifestations Of Severe Dengue and Managementmentioning
confidence: 99%
“…With these criteria, the number of unnecessary hospitalisation was drastically reduced, without a concomitant increase in adverse clinical outcomes. 132 In the following, we focus on the management of severe dengue to reduce mortality. Every travel medicine provider and physician caring for ill returned travellers should be familiar with the clinical management of increased vascular permeability leading to intravascular volume depletion is the hall mark of severe dengue, which may progress to life-threatening dengue shock syndrome.…”
Section: Clinical Manifestations Of Severe Dengue and Managementmentioning
confidence: 99%
“…Periodic switches in the prevailing dengue serotype are associated with dengue epidemics during the peak dengue season 13 and account for a significant burden in terms of hospitalizations. 14 In the week ending May 30, 2020, Singapore reported a record weekly high of 733 dengue cases, a peak not seen since 2013, the largest outbreak year in recent history. 15 Locally, there have been sporadic case reports of COVID-19 initially diagnosed as dengue due to false-positive dengue serology on RDTs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies following the 2002 dengue epidemic in Taiwan [ 22 24 ] found that older and elderly adults are at higher risk of developing severe dengue, previously known as dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS). Investigators in Singapore, Malaysia and Vietnam also demonstrated an increased risk of high clinical severity and case fatality among the older population [ 25 27 ]. As the higher incidence of severe dengue and DHF/DSS cases has led to higher rates of hospitalization, admission to intensive care units (ICUs), and deaths in older adults, especially in the elderly, an effective dengue intervention strategy targeting older and elderly adults in non-endemic areas with DENV infection risk has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%